Comparison of two meridic diets for rearing the coffee berry borer Hypothenemus hampei (Ferrari) - PÉREZ - L., ELSA JEANNETH; BUSTILLO-P., ALEX E.; GONZÁLEZ-G., MARIA TERESA; POSADA-F., FRANCISCO J. (Revista Colombiana de Entomología, 1995)
To rear the coffee berry borer, Hypothenemus hampei, two medic diets have been developed, one in New Caledonia (B) and the other in Mexico (V). The efficiency of these diets was studied under laboratory conditions (T=27 ± 1°C; R.H.=70-80%), using two different containers to test the diet V: laboratory test tubes (V1) and plastic cups (V2) and only cups for diet B. Results showed that the borer develops better in the V diet but less contamination is produced using the plastic cups. The average production (X ± SD) of biological stages per individual successfully reproduced in the different diets, after 40 days, was 12.5 ± 9.38 for B diet, 48.5 ± 21.3 for V2 diet and 55.3 ± 15.9 for Vi. When the average adult production was analyzed, it was found to be 1.38, 13.0, and 15.36, for diets B, V1, and V2, respectively. The diet efficiency measured according to the number of containers in which the insect reproduced successfully was 50.0% for diet V2, 47.72 for V1, and 38.54 for B. The oviposition was greater in diets V1 and V2, reaching a second peak 40 days later, which corresponds to the second generation.